Global Variability of V3 Loop Tetrapeptide Motif: a Concern for HIV-1 Neutralizing Antibodies-based Vaccine Design and Antiretroviral Therapy - Luciano Rodrigo Lopes; Antonio Carlos da Silva Junior; Paulo Bandiera-Paiva; Jorge Casseb (Journal of Medical Microbiology and Infectious Diseases)
Introduction: HIV-1 gp120 V3 GPGR motif has an essential role in viral invasion, cell fusion, and pathogenesis but presents a significant variability that can implicate neutralizing antibodies and antiretroviral drug resistance. Methods: We performed a comprehensive analysis based on 259,288 HIV-1 gp120 amino acid sequences obtained from the Los Alamos National Laboratory (LANL) HIV Sequence Database to infer the global distribution of V3 tetrapeptide motifs. We calculated the frequencies and presented the main variants according to continents and countries. Furthermore, the clinical importance of the most distributed V3 motifs was detailed. Results: Our results showed GPGR and GPGQ as the most commonly found V3 motifs among more than five hundred V3 variant motifs. Motifs with clinical implications are widely distributed around the world. Within the most frequent V3 tetrapeptide motifs set, some variants enable the escape from fusion inhibitor drugs and neutralizing antibodies. Conclusion: Considering that an effective vaccine candidate should elicit broadly neutralizing antibodies while fusion inhibitor drug interaction requires conserved amino acids, the diversity of V3 motifs implicates a great challenge in developing an effective HIV-1 vaccine.